An exploratory study on healthcare sustainability in Turkey: Satisfaction with work environment and perceived barriers towards reducing the environmental impact of pathology operations (Annals of Medical Research, 2021)
Aim: This study aims to determine the self-reported satisfaction of pathologists in Turkey with the physical amenities of their workplace environment, gage their awareness on its potential impacts to human health, and quantify perceived environmental impact of healthcare operations. Moreover, current knowledge and potential interest towards adoption of techniques and materials that reduce environmental impacts of pathology operations including applicable green laboratory techniques, material alternatives with less toxicity, material recycling programs, and reusable equipment were explored through the questionnaire. Material and Methods: For this descriptive study of haphazard sampling, pathologists were invited to complete a 10-question online survey (administered through Google Survey) via Federation of Pathology Societies of Turkey by email and through posts on professional groups on social media. 149 complete responses were received and analyzed as part of the study.Results: With respect to physical conditions, 58%, 44%, and 42% of responders indicated satisfaction with indoor temperature, physical conditions, and amount of daylight of their primary workspace, respectively. 83% indicated they would like to see more recycling of materials and chemicals used in pathology operations, where lack of knowledge and perceived cost were listed as the two main barriers preventing recycling of laboratory chemicals.Conclusion: Results shed light on next steps to improve workplace conditions for pathologists in Turkey and reduce environmental impacts in pathology operations.
Keywords: Sustainability; survey; pathology